Rokok dan Pengaruhnya terhadap Darah - Irma Yanti Rangkuti; Lucia Aktalina (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Cigarettes have a bad impact on health, one of which is the most fundamental to blood, one of that is hematocrit. The goal of research were comparing and correlating cigarettes with hematocrit,used cross sectional design in Mulyasari Subang Village, West Java, 55 male respondents. Respondents who smoked were 27 people. Smoking duration 15.93 years ± 7.54. The type of cigarettes with the most filters, 55.6%. The hematocrit value is 61.8% in the low category, the average is 38.79% ± 6.53. Cigarettes smoked per day 16.7 cigarettes ± 3.58. The average hematocrit in smokers was 35.12% ± 6.09 and 42.34% ± 4.79 in non smokers. The hematocrit of filter smokers was 36.71% ±7.57 and 33.13% ±2.62 in non-filter smokers. There were differences in hematocrit in smokers and non-smokers (p = 0.00; p <0.05). Number of cigarettes per day related to hematocrit (p = 0.043; p <0.05). Smoking duration was not associated with hematocrit (p = 0.55; p > 0.01). There was no difference between the type of cigarette and the hematocrit (p = 0.131, p > 0.05). Hematocrit between smokers and non-smokers were different. Hematocrit related to the number of cigarettes per day. Smoking duration related to hematocrit and hematoc